Reducing prejudice: the role of contact theory in inter-religious dialogue - Ab. Majid, Arfah (Asian Scholars Network, 2020)
Due to prejudicial attitude that is still ingrained in some of Malaysian society, there are always inter-religious issues arise in this country. This detrimental attitude if not being handled wisely could lead to inter-religious discord. Even though inter-religious dialogue has been implemented in Malaysia since 1950s, its effects on prejudice reduction is still vague. International dialogue practitioners have begun to include a number of theories in their dialogue designs in order to address prejudice. One of the theories is contact theory proposed by Gordon Allport (1954). According to Allport, contact that occurs under four specified conditions can generate learning and understanding about others which consequently lead to reduction of prejudice. Therefore, this study aims to explore the existing designs of several inter-religious dialogue programs in Malaysia and to determine to what extent these programs conformed to the contact theory. To gather data on inter-religious dialogue designs and their compliance to contact theory, a case study (i.e. interview and document analysis) had been carried out at two organizations, Institut Kemajuan Islam Malaysia (IKIM) and Inter-faith Spiritual Fellowship (INSaF). Two inter-religious dialogue programs for each organization were studied. The findings from the case study suggests that out of four programs, only one of the programs (i.e., INSaF’s community building) fulfilled all four contact conditions since it applied unconventional design of dialogue which combined workshop, exhibition, Hari Raya celebration and alliance building. The other dialogue programs that applied the format of a forum, public lecture or roundtable dialogue only manage to fulfil three contact conditions namely equal status, common goals, and authority sanction. These conventional formats of dialogue did not provide the opportunity for the cooperative interaction condition to occur among the participants, hence the contact theory was incomplete. In order for the dialogue to achieve the desired goals such increasing inter-religious understanding and reducing prejudice, inter-religious dialogue practitioners and organizations should consider developing a systematic inter-religious dialogue design that is grounded on specific theories such as the contact theory in the future.